FIRES IN MUKURU INFORMAL SETTLEMENTS IN NAIROBI, KENYA: UNINFORMED OR UN-ENFORCED - Odhiambo, Standslause; Michael Kiplagat Aiyabei , (IJRDO - Journal of Social Science and Humanities Research, 2020)
Fire disasters are the most common source of property loss and displacements in Nairobi city informal settlements that have in the recent days become frequent. With the expansion of this slums resulting from population increase that arise from rural urban migration, the situation is likely to deteriorate further. This article examines the level of knowledge in regards to fire prevention, mitigation and response to fire among residents of Mukuru slums in Nairobi and further interrogates the role of policies, laws and regulations relating to fire safety by seeking to draw a line as to whether community lack knowledge relating to fires or it is simply the lack of enforcement by the relevant agencies. To do so, this article engaged the Community Based Disaster Response Units (CBDRT) in Mukuru to support in the administering of questionnaires and or organizing for Focused Group Discussion. The research also involved interviews with relevant government authorities and departments among them the area chief, Red Cross officials and the fire response agencies representative. From this research, it was clear that the community has good level of knowledge on fire safety and they are aware of facts that may compromise their safety in regards to fire. Knowledge and awareness on response mechanism was also good, there is however an evident gap on the enforcement of laws and regulations and it would be interesting to conduct further investigations.